1982
DOI: 10.1007/bf01908316
|View full text |Cite
|
Sign up to set email alerts
|

Adenine nucleotide content and regional function during ischemia and reperfusion in canine ventricular myocardium

Abstract: We have compared in open-chest dogs the evolution of adenine nucleotides and creatine phosphate to that of regional mechanical function during ischemia and reperfusion. Reperfusion restored normal value of creatine phosphate whereas adenine nucleotide level remained depressed. The percentage of systolic shortening, which after occlusion has a zero or negative value, increased to about 20% of control, after reperfusion similarly the pressure-length loop areas decreased to 14.9% of control during ischemia and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Glower et al reported 24 hours of recovery following 15 minutes of ischemia in the conscious dog (9). Kloner et al (18) found long lasting dysfunction after a short period of regional ischemia, and Vial et al (36) as well as a recent paper from our laboratory showed a regional dysfunction for several hours in open-chest dog preparations (13). It was demonstrated by Heyndrickx et al (12) that 5 minutes of ischemia are long enough to produce a prolonged postischemic dysfunction.…”
Section: Regional Functionmentioning
confidence: 88%
“…Glower et al reported 24 hours of recovery following 15 minutes of ischemia in the conscious dog (9). Kloner et al (18) found long lasting dysfunction after a short period of regional ischemia, and Vial et al (36) as well as a recent paper from our laboratory showed a regional dysfunction for several hours in open-chest dog preparations (13). It was demonstrated by Heyndrickx et al (12) that 5 minutes of ischemia are long enough to produce a prolonged postischemic dysfunction.…”
Section: Regional Functionmentioning
confidence: 88%
“…Recovery of function after cardiac arrest may be influenced independently of the tissue concentration of ATP by a variety of factors, such as the use of normal blood or substrate-enriched blood or perfusate, reduction of Ca 2+ -activity in the perfusate, secondary cardioplegia, or reduction of the after-load in the early recovery phase [17]. During regional ischaemia or post-ischaemic reperfusion, an individual correlation between ATP concentration and segmental function of the myocardium could not be demonstrated [19]. Data are available which show that there is no close relationship between the post-ischaemic ATP concentration and the degree of dysfunction on the one hand, and the rate of recovery of both function and nucleotide pool on the other hand [6].…”
Section: [9]-mentioning
confidence: 99%
“…I (1989) function are common findings in reversibly injured myocardium (20,21,36), many authors believe that a causal relationship between these postischemic alterations exists (32,33,39,51). However, there might be only a non-causal coincidence of the time courses in reduction of adeninenucleotides and of basal function (29,30,47,48). Recently a closer relationship between ATP and diastolic function rather than between ATP and systolic function was described (22).…”
Section: Introductionmentioning
confidence: 96%